Bone formation at Ti‐6Al‐7Nb scaffolds consisting of 3D honeycomb frame and diamond‐like carbon coating implanted into the femur of beagles. Issue 9 (11th January 2021) - Kawaguchi, Masahito; Segawa, Ayumu; Shintani, Kazuhiro; Nakamura, Yuka; Ishigaki, Yasuhito; Yonezawa, Katsutaka; Sasamoto, Takeshi; Kaneuji, Ayumi; Kawahara, Norio
Abstract: We fabricated Ti‐6Al‐7Nb bone scaffolds with 5 mm diameter and 20 mm length comprise of a three‐dimensional (3D) honeycomb frame structure of truncated octahedra created by selective laser sintering 3D printing. The honeycomb frame was then coated with 0.1 μm thick diamond‐like carbon (DLC) to increase biocompatibility. A round rod of Ti‐6Al‐7Nb alloy (ASTM F1295) was as a control material. They were implanted into the femur bones of beagles to evaluate bone morphometrics and to investigate changes in the transcriptome of the new bone tissue using DNA microarray analysis and real‐time polymerase chain reaction (PCR). In the present report, the 3D honeycomb material with and without DLC film consisting of a‐C:H is referred to as 3D_a‐C:H and 3D_non, respectively. At 3 weeks after implantation, the 3D_non had more contact between the new and artificial bones compared with the control, and the 3D_a‐C:H had more contact between the new and artificial bones compared with the control and 3D_non. Furthermore, 3D_a‐C:H showed even more new bone compared with the control and 3D_non. At 8 weeks after implantation, more appeared lamellar bone with the 3D_a‐C:H implant than those with the control and 3D_non. The real‐time PCR results at 1 week of implantation revealed higher expression levels of VEGF, RANKL, and NOTCH2 expression with 3D_a‐C:H than with 3D_non and control. As a result of real‐time PCR at 2 weeks of implantation, OPN and CTSK expressions were found to be higher with 3D_a‐C:H and 3D_non than that with the control.